2015
DOI: 10.1007/s00216-015-9046-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enantioselective determination of triadimefon and its metabolite triadimenol in edible vegetable oil by gel permeation chromatography and ultraperformance convergence chromatography/tandem mass spectrometry

Abstract: A novel, sensitive, and efficient enantioselective method for the determination of triadimefon and its metabolite triadimenol in edible vegetable oil, was developed by gel permeation chromatography and ultraperformance convergence chromatography/tandem triple quadrupole mass spectrometry. After the vegetable oil samples were prepared using gel permeation chromatography, the eluent was collected, evaporated, and dried with nitrogen gas. The residue was redissolved by adding methanol up to a final volume of 1 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Currently, there are several methods for the analysis and identification of TDF and TDN, such as gas chromatography (GC; Morais, Rodrigues, Queiroz, Neves, & Morais, 2014), supercritical fluid chromatography (Mai et al, 2019), gas chromatography-flame ionization detection (D. Li, He, Chen, & Hu, 2019), GC-tandem mass spectrometry (GC-MS/MS; Hou, Han, Dai, Yang, & Yi, 2013), high-performance liquid chromatography (HPLC; Kadivar & Aliakbar, 2019), HPLC-MS/MS; (J. Li et al, 2017;Yao et al, 2015), and liquid chromatography-MS/MS (LC-MS/MS); (Liang et al, 2012). These methods are accurate and allow the simultaneous detection of multiple compounds; however, they require expensive equipment and trained professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several methods for the analysis and identification of TDF and TDN, such as gas chromatography (GC; Morais, Rodrigues, Queiroz, Neves, & Morais, 2014), supercritical fluid chromatography (Mai et al, 2019), gas chromatography-flame ionization detection (D. Li, He, Chen, & Hu, 2019), GC-tandem mass spectrometry (GC-MS/MS; Hou, Han, Dai, Yang, & Yi, 2013), high-performance liquid chromatography (HPLC; Kadivar & Aliakbar, 2019), HPLC-MS/MS; (J. Li et al, 2017;Yao et al, 2015), and liquid chromatography-MS/MS (LC-MS/MS); (Liang et al, 2012). These methods are accurate and allow the simultaneous detection of multiple compounds; however, they require expensive equipment and trained professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Carbendazim is a benzimidazole fungicide, while triadimefon is a chloroarene fungicide used in agriculture to control various fungal diseases. It is particularly worth mentioning that triadimefon and its metabolite triadimenol have been simultaneously detected in edible vegetable oil by our former research [ 21 ]. Previous studies have shown that triadimefon and its metabolite triadimenol exhibit clear teratogenic effects and are harmful to the mammalian central nervous system [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…42,43 According to our previous research, the degradation half-lives of triadimefon transferred from rape plants to apicultural products such as pollen, honey and royal jelly were about 0.7, 12.5, and 19.5 days respectively. 8 The fact that only metabolite triadimenol was detected in rapeseed samples might therefore be related to the interval between spraying time and harvest time.…”
Section: Storage Stability Analysismentioning
confidence: 99%
“…7 As a common chloroarene fungicide, triadimefon and its metabolite triadimenol have been simultaneously detected in edible vegetable oil. 8 According to the report, triadimefon and its metabolite triadimenol exhibit clear teratogenic effects, and are hazardous to the mammalian central nervous system. 9 Commission Regulation (EU) 2017/627 of 3 April 2017 has amended Annexes II, III and V to Regulation (EC) No 396/2005 of the European Parliament and of the Council regarding maximum residue levels for triadimenol and triadimefon in oilseeds and oil fruits, such as rapeseeds.…”
Section: Introductionmentioning
confidence: 99%